Impact of obesity on clinical outcomes of v-NOTES hysterectomy: a retrospective study - Yang, Liu; Qilin, Wang; Haiying, Lian; Feng, Pan; Tao, Li; Junqiang, Li (Frontiers in Medicine, 2025)
BackgroundObesity is a global health challenge that complicates gynecological surgery. Vaginal natural orifice transluminal endoscopic surgery (v-NOTES) offers a minimally invasive approach to total hysterectomy (TH), but its safety and efficacy in obese patients remain underexplored.ObjectiveThis study aimed to assess the impact of obesity on the perioperative and clinical outcomes of v-NOTES hysterectomy, accounting for potential confounders.MethodsThis retrospective cohort study analyzed 211 patients who underwent v-NOTES TH between January 2021 and September 2024. Patients were categorized into two groups based on BMI: the control group (BMI < 28 kg/m2, n = 112) and the obesity group (BMI ≥ 28 kg/m2, n = 99). Intraoperative indicators and postoperative outcomes during hospitalization, including operative time, intraoperative blood loss, gastrointestinal recovery, hospital stay, and postoperative complications, were compared. A multivariable regression analysis was used to adjust for confounders. All patients were followed up during hospitalization and at 2 and 6 weeks postoperatively.ResultsObese patients had significantly longer operative times (β = 39.2, p < 0.001), delayed gastrointestinal recovery (time to first flatus: β = 5.8, p = 0.018), and prolonged hospital stays (β = 1.3, p = 0.002). No significant differences were found in intraoperative blood loss, conversion rates, blood transfusion, postoperative complication rates, or total hospitalization costs (limited to the inpatient period; all p > 0.05).Conclusionv-NOTES hysterectomy is a safe and effective option for obese patients, with comparable complication rates to non-obese patients. However, obesity independently contributes to longer operative times and delayed recovery. Targeted perioperative strategies, particularly for improving gastrointestinal recovery, could enhance outcomes in this population.